2015
DOI: 10.1136/bmjopen-2015-008892
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of the Spanish partial smoking ban on cardiovascular and respiratory diseases: methodological issues

Abstract: ObjectiveRecent research has assessed the impact of tobacco laws on cardiovascular and respiratory morbidity. In this study, we also examined whether the association between the implementation of the 2005 Spanish smoking ban and hospital admissions for cardiovascular and respiratory diseases varies according to the adjustment for potential confounders.DesignEcological time series analysis.SettingResidents of Madrid and Barcelona cities (Spain).OutcomeData on daily emergency room admissions for acute myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Most studies of the impact of smoke-free legislation on the incidence of myocardial infarction have relied solely upon data on hospitalizations, 15 17 , 19 , 27 29 , 35 37 , 40 , 44 47 although some have analysed mortality data, either alone or with hospitalization data. 38 , 39 , 48 Here, we employed a population-based approach, combining both hospitalization and mortality data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of the impact of smoke-free legislation on the incidence of myocardial infarction have relied solely upon data on hospitalizations, 15 17 , 19 , 27 29 , 35 37 , 40 , 44 47 although some have analysed mortality data, either alone or with hospitalization data. 38 , 39 , 48 Here, we employed a population-based approach, combining both hospitalization and mortality data.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy avoids many of the pitfalls of before-and-after study designs, particularly their limited capacity to take into account other confounding influences that could concurrently affect the myocardial infarction rate, such as changes in public policy and environmental factors. 17 Because of evidence that smoke-free legislation may also reduce the incidence of cerebrovascular accidents and that coronary and ischaemic cerebrovascular diseases share some pathological mechanisms, 18 , 19 we repeated the analysis for ischaemic stroke. In addition, following other studies that employed diagnostic controls, 19 we repeated our analysis for degenerative disc diseases and colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work [ 29 ], all Poisson models were adjusted for the same confounders in all provinces and included harmonic terms for seasonality in admission rates, indicators for the day of the week, and smoothed functions of temperature, influenza epidemic status, and acute respiratory infection rates. Models for asthma admissions also included smoothed functions of pollen counts.…”
Section: Methodsmentioning
confidence: 99%
“…These findings complement an existing body of literature that has generally indicated that smoke-free policy implementation is associated with lower rates of hospital admissions or mortality for cardiovascular disease. 16,17,[19][20][21][22][27][28][29][30][31][32][33][34][35] Prior studies have typically been ecological in nature [14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][34][35][36] and have not had access to detailed individual-level information on sociodemographic characteristics and cardiovascular disease risk factors. Our findings that patterns were largely similar after controlling for a large number of potential confounders suggest that differences in cardiovascular disease risk among those in areas with and without smoke-free policies are not explained by differences in individual sociodemographics or traditional cardiovascular disease risk factors.…”
Section: Original Research Articlementioning
confidence: 99%
“…Prior studies have used primarily ecological designs, [14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][34][35][36] and have lacked access to detailed individual-level data on sociodemographic characteristics and cardiovascular disease risk factors. Interpretation of results from ecological studies is limited by the potential for unmeasured confounding by individuallevel characteristics, a drawback that could be reduced by using data from ongoing cohort studies.…”
mentioning
confidence: 99%